The facts on file dictionary of organic chemistry - Daintith, John (Facts on file science library, 2004)
Providing a quick access and complete reference to the terms, concepts and principles of organic chemistry. Areas of the subject include basic terms in chemistry, physical chemistry, techniques used in organic chemistry, elements, classes of compounds, and industrial processes.